Pengaruh Perceived Organizational Support (POS) Terhadap Komitmen Afektif Dengan Kepercayaan Organisasi Sebagai Variabel Mediasi - Acep Solihin; Adi Rahmat; Fahmi Oemar; Didik Siswanto (Management Studies and Entrepreneurship Journal (MSEJ), 2025)
This research aims to analyze the influence of Perceived Organizational Support (POS) on affective commitment with organizational trust as a mediating variable in the context of public sector institutions in Indonesia. The study was conducted at the Riau Provincial Youth and Sports Office using a quantitative survey method involving 101 respondents. Data analysis was performed using Partial Least Squares Structural Equation Modeling (SEM-PLS). The results show that POS has a significant positive effect on affective commitment both directly and indirectly through organizational trust. This research confirms that organizational trust plays a mediating role in strengthening the emotional connection between employees and the organization. The findings support Social Exchange Theory and highlight the importance of organizational fairness, supervisory support, and employee welfare in enhancing affective commitment